2021
DOI: 10.3390/biomedicines9111653
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Geometry and Phasic Function Determined by Cardiac Magnetic Resonance Are Independent Predictors for Outcome in Non-Ischaemic Dilated Cardiomyopathy

Abstract: Left atrial (LA) geometry and phasic functions are frequently impaired in non-ischaemic dilated cardiomyopathy (NIDCM). Cardiac magnetic resonance (CMR) can accurately measure LA function and geometry parameters. We sought to investigate their prognostic role in patients with NIDCM. We prospectively examined 212 patients with NIDCM (49 ± 14.2-year-old; 73.5% males) and 106 healthy controls. LA volumes, phasic functions, geometry, and fibrosis were determined using CMR. A composite outcome (cardiac death, ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The median age at baseline was 56 (IQR: 46–64) years, and 81% were men. The LA and RA strain and strain rate (SR) were reduced compared with the corresponding values reported previously in normal subjects 11 . LGE was present in 67.7% of patients.…”
Section: Resultsmentioning
confidence: 44%
See 4 more Smart Citations
“…The median age at baseline was 56 (IQR: 46–64) years, and 81% were men. The LA and RA strain and strain rate (SR) were reduced compared with the corresponding values reported previously in normal subjects 11 . LGE was present in 67.7% of patients.…”
Section: Resultsmentioning
confidence: 44%
“…Cojan‐Minzat et al . reported that LA total strain had independent predictive value for incremental outcome in NIDCM 11 . Dick et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations